(untitled) (El Hilo de la Fabula, 2021)
Since classical antiquity painting has been linked to poetry, but always based on its imitative nature of reality. This link disappears at the end of the 18th century with Lessing’s separation between spatial and temporal arts. In the 20th century, and under protection of Comparative Literature, that connection was re-established. Doležel’s concept of transduction also intervenes, in principle applicable to literature, but extrapolatable to inter-artistic relationships, and means the reproduction with different techniques in each art of the same effects on the receiver. In the avant-gardes of the 20th century, the concept of imitation disappears and in cubism the transduction of techniques is reinforced by the visual-intellectual character of both painting and poetry and by their mixed aspect (collage, graphic arrangement). In certain poems by Pierre Reverdy the techniques that bring him closer to the synthetic cubism of Juan Gris can be seen.